Perforation of Nasal Septum: Etiology and Diagnosis - Fornazieri, Marco Aurélio; Moreira, Jemima Herrero; Pilan, Renata; Voegels, Richard Louis (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: The nasal septum perforation is an occasional finding of rhinoscopy and most patients are asymptomatic. However, there are several possible etiologies of this condition, making necessary a thorough investigation.Objective: To review the literature the main causes of septal perforation and describe the diagnostic tests currently used. Method: A systematic literature review of journals indexed identifiable until December 2008.Final Comments: The main causes are the traumatic / iatrogenic nasal drug use, exposure to toxic gases, inflammatory and infectious diseases and neoplasms. The diagnosis is based on detailed medical history, focusing on occupation and origin of the patient, observation of the characteristics of mucosal injury on biopsy and collection of additional tests such as ANCA, guided by the main suspect.
Keywords: nasal septum; diagnosis; granuloma